Abnormal parietal encephalomalacia associated with schizophrenia: A case report. Issue 10 (March 2017) - Pan, Fen; Wang, Jun-Yuan; Xu, Yi; Huang, Man-Li
Abstract: Rationale: It is widely believed that structural abnormalities of the brain contribute to the pathophysiology of schizophrenia. The parietal lobe is a central hub of multisensory integration, and abnormities in this region might account for the clinical features of schizophrenia. However, few cases of parietal encephalomalacia associated with schizophrenia have been described. Patient concerns and Diagnoses: In this paper, we present a case of a 25-year-old schizophrenia patient with abnormal parietal encephalomalacia. The patient had poor nutrition and frequently had upper respiratory infections during childhood and adolescence. She showed severe schizophrenic symptoms such as visual hallucinations for 2 years. After examining all her possible medical conditions, we found that the patient had a lesion consistent with the diagnosis of encephalomalacia in her right parietal lobe and slight brain atrophy. Interventions: The patient was prescribed olanzapine (10 mg per day). Outcomes: Her symptoms significantly improved after antipsychotic treatment and were still well controlled 1 year later. Lessons: This case suggested that parietal encephalomalacia, which might be caused by inflammatory and infectious conditions in early life and be aggravated by undernutrition, might be implicated in the etiology of schizophrenia.